Ecologia alimentar do peixe-boi da Amazônia (Trichechus Inunguis) (Sirenia, Trichechidae) nas reservas de desenvolvimento sustentável Mamirauá e Amanã - Pazin, Michelle Gil Guterres (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
In order to study the feeding ecology of the Amazonian manatee, we collected 230 fecal samples and analyzed 16 stomach contents of wild manatees during the flooded and low-water periods of the Amazon ecosystem between 1994 and 2008 in the Sustainable Development Reserves of Mamirauá (RDSM) and Amanã (RDSA). The plant species present in the samples were identified from the comparative analysis with an epidermal reference collection of 69 species potentially used by manatees in the Amazon. A total of 49 plant species were identified in the diet of the manatee. The five most common species were Hymenachne amplexicaulis, Oryza grandiglumis, Paspalum repens, Azolla caroliniana and Limnobium spongia. The family with the higher frequency of occurrence was Poaceae, with 91.5%. Plant species of emergent and free-floating habits were the most consumed. We identified 32 plant species in the RDSM, 18 in the low-water season and 28 in the high-water season. In the RDSA, 48 plant species were identified, of which 40 occurred in both periods. There were differences in the composition of plant species found in the feces and stomach contents of manatees between the low- and high-water periods (ANOSIM R = 0.092, p = 0.0002) but not between the várzea and igapó areas. Among the 49 plant species consumed by the manatees, nine plants presented toxic principles, mainly the groups of latex, cyanogenetic, containing saponin, and that accumulate nitrates and nitrites. The presence of invertebrates, seeds, plastic, sand and other unidentified materials were also observed in the feces samples and stomach contents of the Amazonian manatee. According to our results, the Amazon manatee feeds on a wide variety of plant species in both high- and low-water periods and in the várzea and igapó environments, and food supply only does not justify the seasonal migration of the species.
Keywords: Alimentação do Peixe-boi; Ecologia alimentar